Criação de narrativas interculturais em formato de jogos digitais educacionais destinados ao intercâmbio social, cultural e econômico - Oliveira, Fabiana Martins de (2020)
This research proposes and develops an educational videogame addressed to children aged six to nine years old mainly focused on cultural factors. In order to reach this goal, our approach analyzes studies about teaching and learning, particularly in the field of Arts. We also gather information concerning audiovisual production for children as well as the cognitive influences involved in this process. Having selected this theme, our main difficulty resided on the lack of essays and reflections that effectively connect arts, digital culture, childhood, and learning. However, insisting in this purpose aims not only to enhance the children’s relationship with arts, but also formulate questions involving children´s cognitive processes and the constitution of subjectivity during childhoood based on cultural and ludic aspects, especially using vocabularies from Brazilian national folklore. The game produced through this proposal was titled as Cultural Connections